ISSUES OF ORGANIZATION OF ECONOMIC ANALYSIS IN AUTOMOBILE TRANSPORT ENTERPRISES IN THE CONDITIONS OF A PANDEMIC - Ergashev Sherzod Toshpulatovich (Journals Park Publishing, 2022)
In this article, the need to take into account the direction of activity in the organization of economic analysis of automobile transport enterprises in the pandemic and its aftermath, as well as if the motor transport enterprise designed for cargo transportation has been operating intensively during the pandemic, the current order of efficiency indicators in such enterprises information is given that it is necessary to determine according to taking into account that the company is almost inactive during the pandemic, it is proved that the losses and expenses incurred until the end of the period of non-operation due to the pandemic should not be taken into account when calculating the profitability of assets and financial stability.
Keywords: pandemic period, economic analysis, automobile transport enterprises, financial stability, road transport.